Technological Considerations in Measuring Weatherderived Epileptic Seizures of Dogs - Pintér, Ádám; Samu, Krisztián; Czeibert, Kálmán (Recent Innovations in Mechatronics, 2015)
As in every technical discipline, the objective, reproducible instrumental measurements are indispensable. It is no different at investigating the effect of weather on living organism. The parallel measurement of the atmospheric environment and the physiological parameters is novel and individual, as well as the investigation of epileptic seizures depending on weather situations. Several questions came up in connection with our equipment designed for studying dogs epileptic phenomenon, such as fixing, water resistant,- and robust implementation, the problem of data storage, measurement schedule or the power supply for instance. Keeping these in mind during the development process we got an apparatus, which since is an integral part of our further researches.